Assessment of body composition in breast cancer patients: concordance between transverse computed tomography analysis at the fourth thoracic and third lumbar vertebrae - Daly, Alex; Newman, Lydia; Thomas, Alexandra; Munro, Alicia; Spence, Cameron; Long, Joe; Arnott, Jonathan; Durkin, Kesta; Layfield, David; Heetun, Adam; Wootton, Stephen; Copson, Ellen R.; et al. (Frontiers in Nutrition, 2024)
Introduction: Specific body composition markers derived from L3 axial Computed Tomography (CT) images predict clinical cancer outcomes, including chemotherapy toxicity and survival. However, this method is only applicable to those undergoing lumbar (L3) CT scanning which is not universally performed in early breast cancer. This study aimed to evaluate CT analysis at T4 as a feasible alternative marker of body composition in breast cancer.Methods: All patients participated in the Investigating Outcomes from Breast Cancer: Correlating Genetic, Immunological and Nutritional Predictors (BeGIN) observational cohort study (REC reference number: 14/EE/1297). Staging chest-abdomen-pelvic CT scan images from 24 women diagnosed with early breast cancer at University Hospital Southampton were analysed. Adipose tissue, skeletal muscle and muscle attenuation were measured from the transverse CT slices' crosssectional area at T4 and L3. Adipose tissue and skeletal muscle area measurements were adjusted for height. Spearman's rank correlation coefficient analysis was used to determine concordance between body composition measurements using CT analysis at L3 and T4 regions.Results: Derived estimates for total, subcutaneous and intramuscular adipose tissue mass following adjustment for height were highly concordant when determined from cross-sectional areas of CT slices at T4 and L3 (Rs=0.821 p<0.001, Rs=0.816 p<0.001 and Rs=0.830, p<0.001). In this cohort, visceral adipose tissue and skeletal muscle estimates following height adjustment were less concordant when measured by CT at T4 and L3 (Rs=0.477 p=0.039 and Rs= 0.578 p=0.003). Assessment of muscle attenuation was also highly concordant when measured by CT at T4 and L3 (Rs=0.840, p<0.001).Discussion: These results suggest CT analysis at T4 and L3 are highly concordant markers for total adipose, subcutaneous and intramuscular adipose estimation, but not visceral adipose tissue, in this breast cancer population. High concordance between T4 and L3 was also found when assessing skeletal muscle attenuation. Lower concordance was seen for estimates of skeletal muscle area, which differences in the quantity and proportions of axial and appendicular muscle between the thorax and abdomen might explain. Future work will determine the value of T4 metrics as predictive tools for clinical outcomes in breast cancer.